MEFV mutations affecting pyrin amino acid 577 cause autosomal dominant autoinflammatory disease. Issue 2 (16th March 2013) - Stoffels, Monique; Szperl, Agata; Simon, Anna; Netea, Mihai G; Plantinga, Theo S; van Deuren, Marcel; Kamphuis, Sylvia; Lachmann, Helen J; Cuppen, Edwin; Kloosterman, Wigard P; Frenkel, Joost; van Diemen, Cleo C; et al.
Abstract : Objectives: Autoinflammatory disorders are disorders of the innate immune system. Standard genetic testing provided no correct diagnosis in a female patient from a non-consanguineous family of British descent with a colchicine-responsive autosomal dominant periodic fever syndrome. We aimed to unravel the genetic cause of the symptoms. Methods: Whole exome sequencing was used to screen for novel sequence variants, which were validated by direct Sanger sequencing. Ex vivo stimulation with peripheral blood mononuclear cells was performed to study the functional consequences of the mutation. mRNA and cytokine levels were measured by quantitative PCR and ELISA, respectively. Results: Whole exome sequencing revealed a novel missense sequence variant, not seen in around 6800 controls, mapping to exon 8 of the MEFV gene (c.1730C>A; p.T577N), co-segregating perfectly with disease in this family. Other mutations at the same amino acid (c.1730C>G; p.T577S and c.1729A>T; p.T577S) were found in a family of Turkish descent, with autosomal dominant inheritance of familial Mediterranean fever (FMF)-like phenotype, and a Dutch patient, respectively. Moreover, a mutation (c.1729A>G; p.T577A) was detected in two Dutch siblings, who had episodes of inflammation of varying severity not resembling FMF. Peripheral blood mononuclear cells from one patient of the index family showed increased basal interleukin 1β mRNA levels and cytokine responses after lipopolysaccharide stimulation. Responses normalised with colchicine treatment. Conclusions: Heterozygous mutations at amino acid position 577 of pyrin can induce an autosomal dominant autoinflammatory syndrome. This suggests that T577, located in front of the C-terminal B30.2/SPRY domain, is crucial for pyrin function.